Upaya Meningkatkan Hasil Belajar Siswa Sekolah Dasar Materi Menyambut Usia Baligh - Darkasih Darkasih; Azizah Aryati (Jurnal Indonesia Kajian Pendidikan Islam, 2025)
Background: This study was motivated by issues in Islamic Religious Education (PAI) lessons at SDN 045/V Teluk Nilau, particularly about "Welcoming Puberty." Objective: This study aims to improve the learning outcomes of fourth-grade students by applying the Problem-Based Learning (PBL) model to the topic of "Welcoming Puberty." Method: The method used in this study was a quantitative approach with data collection through observation and testing. The respondents in this study were 12 fourth-grade students at SDN 045/V Teluk Nilau. Result: The application of the PBL model can increase students' interest in learning, understanding of concepts, and motivation, which has an impact on improving their learning outcomes. Based on the test results, students significantly improved their understanding of the material taught. Conclusion: The PBL model effectively improves students' learning outcomes on the material "Welcoming Puberty" and positively impacts students' interest and motivation to learn. Contribution: This study contributes insights for teachers to apply more interactive and relevant learning models, which can improve the quality of Islamic Education learning in elementary schools and open opportunities for further research in developing more varied and effective learning methods.